Floral biometrics and phenological characterization of flowering and fruiting of the passion fruit Passiflora trintae in southwestern Bahia, Brazil - dos Santos Lemos Filho, Danilo; de Lima Santos, Mariana; Carlos da Mota Porto, Antonio; Lima, Rômulo Pedro Macêdo [UNESP]; Carlos de Oliveira, Antonio (Editora Letra1, 2023)
A positive influence of temperature and precipitation was observed on floral and fruit development of Passiflora trintae Sacco. This study described the floral biometrics and characterized the reproductive phenology based on local climatic factors (temperature and precipitation) of a natural population of P. trintae in southwestern Bahia State, Brazil. According to the floral morphometry results, data were obtained that can be used in future taxonomic studies and for exploring diversity by making interspecific crosses with other species of the same genus. Under the study conditions, a higher production of flower buds and flowers at anthesis, as well as flowering peak, occurred during the summer months, while a higher production of ripe and immature fruits, as well as fruiting peak, coincided and occurred during the spring. The period of floral anthesis begins at around 04:30 a.m. and ends at around 04:00 p.m. Temperature can predict the phenological variables of flowering peak and flower bud rate, while precipitation can predict all phenological variables related to flower bud rate, flowering rate, flowering peak, fruiting rate, and fruiting peak.
Biometria floral e caracterização fenológica da floração e frutificação para o maracujá Passiflora trintae no Sudoeste da Bahia, Brasil
Keywords: anthesis; floral descriptors; passion fruit; phenology